How is the manifest nullity provided for in article 220 of the Civil Code declared? a forty-year old problem - Ninamancco Córdova, Fort (2024)
Article 220 of the Civil Code allows the judge to declare ex officio the nullity of a legal act, but only if it is ‘manifest’. This capacity of the judge has generated two important questions: what steps must the judge follow to declare the nullity ex officio; and how can a manifest nullity be distinguished from a non-manifest nullity?In this line, the author of this paper addresses the first question by making an extensive analysis of what is set forth in different case law (files of the Tribunal and Plenary Cassations). However, there is a great deal of work ahead in terms of the standardization of the jurisprudence as well as to achieve a correct articulation between this and the doctrine.Thus, the author highlights the idea and the need to find a mechanism of steps for the declaration of nullity that contemplates the principles of due process and at the same time is restrictive and efficient in the face of the uses of the parties.